Being a Parent after a Disaster: The New Normal after the 2009 Victorian Black Saturday Bushfires. (27th July 2021) - Kosta, Lauren; Harms, Louise; Gibbs, Lisa; Rose, David
Abstract : Parenting can be tough at the best of times but what is it like after a disaster? We spoke to mothers and fathers nearly seven years after the 2009 catastrophic bushfires in Victoria, Australia. They shared incredibly personal stories about the trauma, loss, and disruption caused by the fires, and ways in which they responded as parents. For many of those we spoke to, the experience was one of losing what had been normal. In the aftermath of the fires they were managing exposure to further stress and trauma, feeling as though the ability to have fun was gone, and living at capacity as demands competed for their time and energy. They worked hard to settle their families and regain a sense of normal, aiming to provide stability and familiarity, and manage their own emotions. They explained the pressure they felt around the need to settle, and that recovery took some several years or was ongoing. Understanding what this experience can be like will help social workers think about how to support parents and their families in finding their new normal after disasters. Abstract: This article explores parental experiences over nearly seven years that followed catastrophic Australian bushfires in 2009. Principles of pragmatism and the constructionist tradition guided the use of semi-structured interviews with parents (nineteen mothers and three fathers) and inductive thematic analysis to distil what participants said about the trauma, loss and disruption caused by the fires, and ways in which they responded as parents. Changes described in their parenting role and family life were themed as 'losing normal' which encompassed managing additional exposures, losing fun and living at their capacity. Parents then evinced the struggle of settling and seeking to regain a sense of normal. This theme highlighted tensions, pressures and expectations they faced (their own and external) in trying to get back to normal, along with extended recovery timeframes. Participants valued strategies to provide stability, familiarity and manage their own emotions. The analysis highlights the influence of the parental role on an experience of trauma, the range of losses and the extended experience of disaster recovery for parents. Insights for social work practice are discussed, including the potential to inform expectations of recovery timeframes and supporting parents and their families to reconstruct their sense of normal in their new, post-disaster context.